Perancangan Panyacah Awig Rejang Pala dalam Penguatan Ekosistem Tari Rejang Pala - Ida Ayu Wayan Arya Satyani; I Wayan Adi Gunarta (Jayapangus Press, 2022)
The Karangasem district has a wealth of rejang rituals spreading throughout several of its sub-districts and handed down through the ages to these days. The community’s constancy in preserving the rejang tradition is a true reflection of the power of written and unwritten set of customary rules (awig-awig). The Rejang Pala from the traditional village of Nongan in the sub-district of Rendang, in the district of Karangasem disappeared in 1917 following the terrifying earthquake that hit Bali on that year. It is therefore imperative that its existence in the village written awig-awig should be restored. The aim of this is to strengthen the dance ecosystem after a reconstructed choreography was successfully made in 2019. Efforts to include the rejang as part of the awig-awig should be preceded by planning the design of the payacah awig, that is, an elaboration of article after article of the awig-awig by means of a research applying a qualitative methodology. Observation should be carried out in several ancient villages where the tradition of rejang has been handed down, complemented with interviews, literature studies and documentation. The data analysis and the compilation of the report should be descriptive. The outcome of the research should include the following elements of the Rejang Pala’s panyacah awig, formulated through: 1) a self-critic of the reconstruction process up to the launching of the dance (makebah); 2) an inquiry into whatever rules pertaining to the planning and design of the Rejang Pala’s panyacah awig in line with the characteristics of the local villages and 3) formulation of the design of the Rejang Pala’s panyacah awig in line with the characteristics of the local villages. Finally, it is hoped that the design of the panyacah awig will result in the revival of the Rejang Pala for the benefit of the culture and the welfare of the custodians of this cultural heritage.